The Absence of the Calcium-buffering Protein Calbindin is Associated with Faster Age-related Decline in Hippocampus Metabolism - Moreno, Herman (2011)
Although reductions in the expression of the calcium-buffering proteins calbindin D-28K (CB) and parvalbumin (PV) have been observed in the aging brain, it is unknown whether these changes contribute to age-related hippocampal dysfunction. To address this issue, we measured basal hippocampal metabolism and hippocampal structure across the lifespan of C57BL/6J, calbindin D-28k knockout (CBKO) and parvalbumin knockout (PVKO) mice. Basal metabolism was estimated using steady state relative cerebral blood volume (rCBV), which is a variant of fMRI that provides the highest spatial resolution, optimal for the analysis of individual subregions of the hippocampal formation. We found that like primates, normal aging in C57BL/6J mice is characterized by an age-dependent decline in rCBV-estimated dentate gyrus metabolism. Although abnormal hippocampal fMRI signals were observed in CBKO and PVKO mice, only CBKO mice showed accelerated age-dependent decline of rCBV-estimated metabolism in the dentate gyrus. We also found age-independent structural changes in CBKO mice, which included an enlarged hippocampus and neocortex as well as global brain hypertrophy. These metabolic and structural changes in CBKO mice correlated with a deficit in hippocampus-dependent learning in the active place avoidance task. Our results suggest that the decrease in CB that occurs during normal aging is involved in age-related hippocampal metabolic decline. Our findings also illustrate the value of using multiple MRI techniques in transgenic mice to investigate mechanisms involved in the functional and structural changes that occur during aging.